Synthesis of highly stable Ag/Ta2O5 nanocomposite by pulsed laser ablation as an effectual antibacterial agent. (July 2023) - Alheshibri, Muidh; Kotb, Essam; A.Haladu, Shamsuddeen; Al Baroot, Abbad; Drmosh, Q.A.; Ercan, Filiz; Çevik, Emre; Elsayed, Khaled A.
Highlights: Synthesis of Ag/Ta2 O5 nanocomposite by laser ablation in liquid. Stability of Ag/Ta2 O5 nanocomposite. High performance antibacterial activity of Ag/Ta2 O5 nanocomposite against gram-positive and gram- negative bacteria. Abstract: Enhancing the stability of nanoparticles in colloids has great potential for biological applications. Herein, stable nanoscale antibacterial materials based on silver and tantalum oxide (Ta2 O5 ) were successfully synthesized by a reproducible, simple, surfactant-free, and self-templating approach termed pulsed laser ablation in liquids. The synthesized nanocomposite Ag/Ta2 O5 was characterized using X-ray diffraction (XRD), Raman spectroscopy, scanning electron microscopy (SEM), transmission electron microscopy (TEM), and UV–vis spectrophotometer. The Ag/Ta2 O5 nanocomposite showed excellent dispersion stability for 90 days. Upon assessment of the newly prepared nanocomposites for their biological activity against some bacterial pathogens including Staphylococcus aureus subsp. aureus ATCCBAA-977 and Pseudomonas aeruginosa ATCC27853 using the agar plate diffusion, the results demonstrated that Ag/Ta2 O5 nanocomposite has the highest antibacterial activity compared to the pristine Ag and Ta2 O5 nanoparticles.